2014
DOI: 10.1007/s12274-014-0490-3
|View full text |Cite
|
Sign up to set email alerts
|

Direct measurement of the Raman enhancement factor of rhodamine 6G on graphene under resonant excitation

Abstract: Graphene substrates have recently been found to generate Raman enhancement. Systematic studies using different Raman probes have been implemented, but one of the most commonly used Raman probes, rhodamine 6G (R6G), has yielded controversial results for the enhancement effect on graphene. Indeed, the Raman enhancement factor of R6G induced by graphene has never been measured directly under resonant excitation because of the presence of intense fluorescence backgrounds. In this study, a polarization-difference t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 28 publications
2
32
0
Order By: Relevance
“…On one hand, a comparison among the AEFs from the different samples reveals a significant enhancement effect when nanocrystalline titania and graphene sheets are integrated in the same matrix. The green bars in Figure 5b are accountable for a pure GERS effect, since the silica matrix does not affect the Raman enhancement, and return values ranging from 2.8 to 3.1, which are comparable with those reported in the literature for Raman enhancement of Rh6G signals deposited on graphene 11. On the other hand, the ERS effect from a nanoanatase titania matrix is clearly higher (from 8.7 to 11) than GERS from graphene, even if a direct comparison should be done with care because of the different active interfaces which are involved in the two materials.…”
supporting
confidence: 86%
“…On one hand, a comparison among the AEFs from the different samples reveals a significant enhancement effect when nanocrystalline titania and graphene sheets are integrated in the same matrix. The green bars in Figure 5b are accountable for a pure GERS effect, since the silica matrix does not affect the Raman enhancement, and return values ranging from 2.8 to 3.1, which are comparable with those reported in the literature for Raman enhancement of Rh6G signals deposited on graphene 11. On the other hand, the ERS effect from a nanoanatase titania matrix is clearly higher (from 8.7 to 11) than GERS from graphene, even if a direct comparison should be done with care because of the different active interfaces which are involved in the two materials.…”
supporting
confidence: 86%
“…3a ). Dipping, dropping and thermal evaporation are commonly used methods to deposit target molecules on SERS substrates 8 , 17 , 34 . Here, in order to avoid the uncertainty arisen from different numbers of adsorbed molecules or undesired molecule aggregation, we used vacuum thermal evaporation to deposit 0.2 nm thick R6G, copper phthalocyanine (CuPc), or Protopphyrin IX (PPP) molecules on the testing substrates.…”
Section: Resultsmentioning
confidence: 99%
“…The results show that the EF varies from 5.5 to 63.5 for different vibrational modes. 20 Deng et al 21 reported the EF of R6G on graphene ranging between 1.7 and 5.6 for four Raman modes. In most cases, the EFs of GERS range between 0.3 and 10 2 .…”
Section: Gersmentioning
confidence: 99%
“…20,29−31 In addition, the dependences of the GERS effect on the laser wavelength and polarization are considered. 21,28 Before discussing the characteristics of the GERS effect, it is worth mentioning that the interference effect from the SiO 2 /Si substrate, which we commonly used to support graphene, plays an important role in observing the Raman signal. 19 Strong interference enhancement occurs at 300 nm of SiO 2 layer, which is ideal to observe the Raman signal from both GERS and non-GERS systems and shows the EFs for some molecules.…”
Section: Gersmentioning
confidence: 99%
See 1 more Smart Citation